Factors Affecting Preservice Teachers' Efficacy to Assess Students in Inclusive Classrooms - Sasha Nandlal (Canadian Society for Studies in Education, 2024)
This study aimed to determine the correlation between the factors affecting preservice teachers' efficacy in conducting assessments in inclusive classrooms. The study used a correlational survey questionnaire with 44 student teachers at a tertiary institution in Prince Edward Islands, Canada. The results from the survey were analyzed using the Statistical Package for Social Sciences (SPSS) 27.0. Using statistical software, data was interrogated and analyzed using descriptive statistics analysis and bivariate correlation. The study's sample revealed a significant statistically positive correlation between several factors and teacher efficacy in conducting assessments in an inclusive classroom. These results complement existing findings and are discussed further.